PERILAKU KEUANGAN KELUARGA DENGAN PENDEKATAN SAKINAH FINANCE DALAM MEWUJUDKAN STABILITAS SISTEM KEUANGAN - Eny Latifah; Invony Dwi Aprilisanda (BAJ: Behavioral Accounting Journal, 2020)
This study aims to determine the financial behavior of Muslim families by using the sakinah finance approach which specifically creates the stability of the internal family financial system and in general creates the financial stability of the State. This research method uses a qualitative approach that is descriptive. This study describes the behavior of Islamic family finance by combining the analysis of interview results and observations obtained from family accounting. The results showed that not all of the Muslim families applied the sakinah finance approach in family financial management so that the family's financial stability was often unstable and triggered debt and made a mortgage on their property.